Efektivitas Model Pembelajaran Berbasis Proyek dalam Peningkatan Berpikir Kreatif Siswa pada Pembelajaran IPS Sekolah Dasar - Nurbayanti, Rika; Ismail, Muhammad; Somantri, Mubarok; Nurdiansyah, Nurdiansyah; Nurbayan, Yayan (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the project-based learning model in improving students' creative thinking skills in Social Studies (IPS) learning at the elementary school level. The method used is a quasi-experimental design with a non-equivalent control group. The research subjects were fifth-grade students at SDN Cihambulu I, Subang Regency. The study involved two groups: the experimental group and the control group. The experimental group received instruction using the Project-Based Learning (PjBL) model, while the control group received Direct Instruction. Data collection was carried out using tests. The analysis results showed a significance value (2-tailed) of 0.001, which is below the threshold of 0.05, indicating a significant difference between the two groups. Furthermore, the average N-Gain Score of 0.86 demonstrates a high level of improvement. It can be concluded that the project-based learning model effectively enhances students’ creative thinking skills in Social Studies learning at the elementary school level.